Time trends in anxiety disorders incidence across the BRICS: an age-period-cohort analysis for the GBD 2021 - Liu, Dan; Luo, Murong; Huang, Yan; Tan, Yingfang; Cheng, Fangqun; Wu, Yuhang (Frontiers in Public Health, 2024)
Background: Anxiety disorders are a significant global mental health concern, contributing to substantial disability-adjusted life years (DALYs) and imposing considerable social and economic burdens. Understanding the epidemiology of anxiety disorders within the BRICS nations (Brazil, Russian Federation, India, China, and South Africa) is essential due to their unique socio-economic landscapes and ongoing transformations.Methods: This study utilized data from the Global Burden of Disease (GBD) 2021 database to evaluate anxiety disorder incidence trends in BRICS countries from 1992 to 2021. The Age-Period-Cohort (APC) model with an intrinsic estimator (IE) algorithm was employed to disentangle the effects of age, period, and cohort on incidence rates. Data were categorized into 5-year age groups, and 95% uncertainty intervals (UIs) were calculated to account for data variability.Results: From 1992 to 2021, the global number of anxiety disorders cases increased by 42.34%, with age-standardized incidence rates rising by 21.17%. Among BRICS nations, India experienced the largest increase in cases (113.30%), while China had the smallest increase (2.79%). Globally, young (15-49 years) and oldest (80-94 years) age groups showed predominantly positive local drift values, indicating rising incidence rates. Brazil and India mirrored this trend, while China and South Africa mostly exhibited negative local drift values. Russia Federation had mixed trends with younger groups showing negative and older groups positive local drift values. The incidence of anxiety disorders exhibited an "M-shaped" age pattern with peaks at 10-14 and 35-39 years. Period effects were stable globally but varied in BRICS countries, with Brazil showing a decline and India an increase. Cohort effects were stable globally but showed increasing trends in Brazil and India post-1955-1959 cohort.This study highlights a significant increase in anxiety disorders incidence globally and within BRICS nations over the past three decades, with marked variations across countries. The distinct trends observed in age, period, and cohort effects call for age-specific and gender-sensitive mental health policies. Continuous monitoring, research, and tailored public health strategies are essential to address the rising burden of anxiety disorders and improve mental health outcomes in these rapidly evolving regions.